Perbedaan Tingkat Pengetahuan Kaidah Dasar Bioetika Pada Mahasiswa Fakultas Kedokteran Universitas Andalas - Raditya Arya Dewanda; Taufik Hidayat; Avit Suchitra (Fakultas Kedokteran, Universitas Andalas, 2022)
Basic principles of bioethics are one of the materials taught to medical students. With a sufficient level of knowledge regarding the basic principles of bioethics, doctors can treat patients properly and optimally. This study aims to determine the differences in the level of knowledge of the application of the basic principles of bioethics in medical practice among students of the Faculty of Medicine, University of Andalas. This research is an observational analytic study with a cross sectional study design and the sampling technique using consecutive sampling technique, which obtained a total of 243 respondents. The research data is in the form of primary data using the Questionnaire Tes Kaidah Dasar Bioetika as a measuring tool with the measurement results obtained will be worth 0-8 and are considered to have good knowledge if you get a score of >5. Data analysis used bivariate analysis oneway ANOVA and Independent T test. The results of the study found that respondents who had good knowledge amounted to 29% in class 2017, 20% in class 2018, and 10% in class 2019, with a total percentage of 20% and there was a significant difference in the mean value of knowledge levels based on the year of entry and type which class 2017 is higher than the lower class and female students score higher than male students. The conclusion of this study is that the class that entered earlier had a better level of knowledge than the lower class because of education factors and female students had a better level of knowledge than male students because females were better at taking steps that related to ethics.